Preliminary Psychometrics for the Executive Function Challenge Task: A Novel, "Hot" Flexibility, and Planning Task for Youth. (17th August 2020) - Kenworthy, Lauren; Freeman, Andrew; Ratto, Allison; Dudley, Katerina; Powell, Kelly K.; Pugliese, Cara E.; Strang, John F.; Verbalis, Alyssa; Anthony, Laura G.
Abstract: Objective: Executive functions (EF) drive health and educational outcomes and therefore are increasingly common treatment targets. Most treatment trials rely on questionnaires to capture meaningful change because ecologically valid, pediatric performance-based EF tasks are lacking. The Executive Function Challenge Task (EFCT) is a standardized, treatment-sensitive, objective measure which assesses flexibility and planning in the context of provocative social interactions, making it a "hot" EF task. Method: We investigate the structure, reliability, and validity of the EFCT in youth with autism (Autism Spectrum Disorder; n = 129), or attention deficit hyperactivity disorder with flexibility problems ( n = 93), and typically developing (TD; n = 52) youth. Results: The EFCT can be coded reliably, has a two-factor structure (flexibility and planning), and adequate internal consistency and consistency across forms. Unlike a traditional performance-based EF task (verbal fluency), it shows significant correlations with parent-reported EF, indicating ecological validity. EFCT performance distinguishes youth with known EF problems from TD youth and is not significantly related to visual pattern recognition, or social communication/understanding in autistic children. Conclusions: The EFCT demonstrates adequate reliability and validity and may provide developmentally appropriate, treatment-sensitive, and ecologically valid assessment of "hot" EF in youth. It can be administered in controlled settings by masked administrators.